Convergent Validity of Zulliger-CS with the Social Skills Inventory for the Elderly - Grazziotin, Jucelaine Bier Di Domenico; Scortegagna, Silvana Alba (Paidéia (Ribeirão Preto), 2018)
Psychological evaluation instruments need to demonstrate their usefulness to respond to social problems and according to the reality of people. This study aimed to find evidence of convergent validity of the interpersonal relationship indicators and the cognitive triad of the Zulliger in the Comprehensive System (ZSC) with the Social Skills Inventory for the Elderly (IHSI Del-Prette). The sample consisted of 78 elderly individuals, between 60 and 96 years old (M = 76.07). As instruments, the sociodemographic and health characterization protocol was used, the Mental State Mini-Exam, the ZSC and the IHSI-Del-Prette. Pearson’s correlation showed significant associations of the variables of the interpersonal relationship (PER), contents (Cg, A%) and cognitive triad (R, D, XA%, S-, X +%) of the ZSC, with the general score G and the IHSI Del-Prette factors F4, F2, F3 and F1. The results show the convergent validity of ZSC with IHSI Del-Prette.